PP.LB02.08: INCORRECT POSITIONING OF CUFF FOR BLOOD PRESSURE MEASUREMENT. CLINICAL RELEVANCE AND USEFULNESS OF NOVEL CUFF DESIGN. (June 2015) - Bilo, G.; Sala, O.; Perego, C.; Zorzi, C.; Ochoa-Munera, J.E.; Gluszewska, A.; Gao, L.; Vergani, C.; Lonati, L.M.; Parati, G.
Abstract : Objective: Scientific societies and manufacturers recommend that arm cuff for blood pressure (BP) should be placed with the bladder centred above brachial artery for correct measurement. Although cuff malpositioning may be common it is not clear whether the related error is relevant. This study is aimed to address this issue and to evaluate the usefulness of a novel arm cuff to overcome the problem of incorrect cuff positioning. Design and method: An interim analysis in 28 (out of 50 planned) subjects was performed (age 51.2 ± 16.9, 11 M/17F, BMI 29.4 ± 5.2 kg/m2, arm circumference 31.4 ± 3.1 cm). Two sequences of BP measurements on both arms were performed in each participant: 1) with two mercury sphygmomanometers (device A, always correctly placed, Device B either in correct position, rotated by 90° medially, by 90° laterally and by 180°); 2) with a mercury sphygmomanometer (Device A always in correct position) and an Omron M6-Comfort (HEM-7321-E) validated oscillometric device coupled with IntelliWrap cuff (device B, in correct position, rotated by 90° laterally and by 180°). Results: Mean differences are shown in Table, respectively for sequence 1 (two mercury devices, as above) and sequence 2 (BP with Omron M6-Comfort with cuff in different positions minus BP obtained with a reference mercury device having cuff correctly positioned). Figure. No caption available. Conclusions: Interim results show that incorrect conventional cuff positioning significantly affects BP measurement results, with BP overestimation when the bladder centre is displaced by 90° laterally or by 180° compared to correct position. No effect of cuff position was observed when IntelliWrap cuff was used, although BP values obtained with oscillometric device tended to be lower than those obtained by reference method (possibly because of relative undercuffing with mercury device in subjects with large arm circumference).